Profil Anak Tunagrahita Ringan Kelas VIII Mampu Membuat Kembang Goyang Di SLB Negeri 2 Kota Pariaman - Rahma, Nensy Zutria; Efendi, Jon (Universitas Negeri Padang, 2023)
This research discusses how mild mentally retarded children are able to make kembang goyang. The purpose of this research is to describe how Dela is able to make kembang goyang and also as a reference for other parents who have mild mentally retarded children who are able to develop the abilities of mentally retarded children based on local wisdom. This study uses qualitative research with a qualitative descriptive approach, using observation, interviews and documentation. The results of this study indicate that with the abilities possessed by children, they are able to run optimally if they are given trust and practice consistently and use spare time that is consistent with the interests and talents of children based on local wisdom.